Discrete Event Simulation Approach for Pharmaceutical Industry Calibration Laboratory Service Digital Twin Model - Amrih, Pitoyo; Widyo Laksono, Pringgo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This research aims to develop a simulation theory using discrete event simulation as a convincing tool for building a digital twin models in the pharmaceutical industry calibration department as part of the supporting components enabler for industry 4.0. The Methodology used are define the Calibration Laboratory service model, then analyze the big data collected from the service performance parameters. The analyzed data will be used to continue the development of discrete event simulation models for calibration laboratory service systems using ProModel2016 software. The simulation output data will be verified with real event data to ensure similarity. The study finds that the Discrete Event Simulation approach can be used as a convincing tool to develop digital twin models as virtual replicas of Calibration Laboratory Services in the Pharmaceutical Industry so that improvement planning can be analyzed efficiently. There is a limitation of this research that the digital twin model can only be verified for the Pharmaceutical Industry Calibration Laboratory Services as a case study object. Further research needs to be carried out to expand the possibilities of using this discrete event simulation approach for Digital Twin Model in every aspect of industrial activities.